Loss of phosphatase CTDNEP1 potentiates aggressive medulloblastoma by triggering MYC amplification and genomic instability - Luo, Zaili; Xin, Dazhuan; Liao, Yunfei; Berry, Kalen; Ogurek, Sean; Zhang, Feng; Zhang, Liguo; Zhao, Chuntao; Rao, Rohit; Dong, Xinran; Li, Hao; Yu, Jianzhong; et al. (Nature Communications, 2023)
MYC-driven medulloblastomas are highly aggressive childhood brain tumors, however, the molecular and genetic events triggering MYC amplification and malignant transformation remain elusive. Here we report that mutations in CTDNEP1, a CTD nuclear-envelope-phosphatase, are the most significantly enriched recurrent alterations in MYC-driven medulloblastomas, and define high-risk subsets with poorer prognosis. Ctdnep1 ablation promotes the transformation of murine cerebellar progenitors into Myc-amplified medulloblastomas, resembling their human counterparts. CTDNEP1 deficiency stabilizes and activates MYC activity by elevating MYC serine-62 phosphorylation, and triggers chromosomal instability to induce p53 loss and Myc amplifications. Further, phosphoproteomics reveals that CTDNEP1 post-translationally modulates the activities of key regulators for chromosome segregation and mitotic checkpoint regulators including topoisomerase TOP2A and checkpoint kinase CHEK1. Co-targeting MYC and CHEK1 activities synergistically inhibits CTDNEP1-deficient MYC-amplified tumor growth and prolongs animal survival. Together, our studies demonstrate that CTDNEP1 is a tumor suppressor in highly aggressive MYC-driven medulloblastomas by controlling MYC activity and mitotic fidelity, pointing to a CTDNEP1-dependent targetable therapeutic vulnerability.
Gesehen am 29.11.2023